2002
DOI: 10.1074/jbc.m107876200
|View full text |Cite
|
Sign up to set email alerts
|

Mertk Triggers Uptake of Photoreceptor Outer Segments during Phagocytosis by Cultured Retinal Pigment Epithelial Cells

Abstract: The RCS rat is a widely studied model of recessively inherited retinal degeneration. The genetic defect, known as rdy (retinal dystrophy), results in failure of the retinal pigment epithelium (RPE) to phagocytize shed photoreceptor outer segment membranes. We previously used positional cloning and in vivo genetic complementation to demonstrate that Mertk is the gene for rdy. We have now used a rat primary RPE cell culture system to demonstrate that the RPE is the site of action of Mertk and to obtain functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(154 citation statements)
references
References 26 publications
5
149
0
Order By: Relevance
“…This resulted from either RPE uptake of lone QT or phagocytosis of PPC-graft containing QT. The latter scenario was observed in vitro here (Figure 3f) and in others studies 21,22 and is expected given the RPE's phagocytic roles. 23 …”
Section: Graft Survival and Qt Locationsupporting
confidence: 57%
“…This resulted from either RPE uptake of lone QT or phagocytosis of PPC-graft containing QT. The latter scenario was observed in vitro here (Figure 3f) and in others studies 21,22 and is expected given the RPE's phagocytic roles. 23 …”
Section: Graft Survival and Qt Locationsupporting
confidence: 57%
“…It is established that binding of POS to RPE cells activates a hierarchy of tyrosine kinases that are essential for phagosome internalization, and that FAK and MerTK play prominent roles in this process (Feng et al, 2002;Finnemann, 2003). Because FAK and anx A2 are substrates for several tyrosine kinases, including Src (Bellagamba et al, 1997), and because we have recently shown that anx A2 is required for the plasma membrane targeting and activation of Src (Hayes and Moss, 2009), we next tested whether anx A2 and c-Src become tyrosine-phosphorylated during POS phagocytosis by ARPE19 cells.…”
Section: Anx A2 Is Recruited To the Forming Phagosomementioning
confidence: 99%
“…Intriguingly, engagement of the ␣v␤5 integrin by its cognate ligand, milk fat globule-EGF8 (MFG-E8), is essential for the circadian synchronization of phagocytosis (Nandrot and Finnemann, 2006;Nandrot et al, 2007), and although phagocytosis of POS occurs in MFG-E8 Ϫ/Ϫ and ␤5 Ϫ/Ϫ mice, in both mutants the daily rhythm is absent. In contrast, focal adhesion kinase (FAK) and MerTK are not required for the initial binding of POS to the apical surface of the RPE, but they are sequentially activated by ␣v␤5 receptors and are essential for phagosome internalization (Feng et al, 2002;Finnemann, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we still do not know which RPE proteins serve as substrates for MerTK's kinase activity during RPE phagocytosis. However, both endogenous and overexpressed MerTK reveal a striking redistribution to the sites of internalized POS in in vitro phagocytosis assays suggesting that MerTK receptors may be components of the phagocytic machinery of the RPE (Feng et al, 2002;Finnemann, 2003 residues of MerTK in RPE in culture (Feng et al, 2002;Finnemann, 2003). Although their mutual dependence has not been demonstrated directly, levels of MerTK tyrosine phosphorylation commonly serve to assess the extent of MerTK activity.…”
Section: Role Of Mertk Activation In Rpe Phagocytosismentioning
confidence: 99%